Interactions Between Nucleosomes: From Atomistic Simulation to Polymer Model - Zhang, Chengwei; Huang, Jing (Frontiers in Molecular Biosciences, 2021)
The organization of genomes in space and time dimensions plays important roles in gene expression and regulation. Chromatin folding occurs in a dynamic, structured way that subject to biophysical rules and biological processes. Nucleosomes are basic unit of chromatin in living cells, and here we report on the effective interactions between two nucleosomes in physiological conditions using explicit-solvent all-atom simulations. Free energy landscapes derived from umbrella sampling simulations agree well with recent experimental and simulation results. Our simulations reveal the atomistic details of the interactions between nucleosomes in solution, and can be used for constructing the coarse-grained model for chromatin in a bottom-up manner.